PENGEMBANGAN MEDIA ANIMASI BERBENTUK VIDEO MATERI KISAH KETELADANAN WALI SONGO PADA PEMBELAJARAN PAI DAN BUDI PEKERTI KELAS IV SD - Ridho, Muhammad; Azis, Abdul; Muzakki (Rabbani: Jurnal Pendidikan Agama Islam, 2023)
The background of this research is the fourth grade students at SDN 5 Panarung who are still unable to remember the names of the Wali Songo and the behavior that can be exemplified from the story of Wali Songo, the limited use of learning media in the learning process of PAI and Budi Pekerti and material about the story of Wali Songo's Example. is materialabstract so pictures are needed, not just theory/material. This study aims to describe the process of developing shaped animation mediavideo material for Wali Songo's exemplary story in PAI learning and Budi Pekerti Class IV SD and describes the feasibility of shaped animation media products video material for the Story of Wali Songo's Exemplary in Islamic Education and Class IV Elementary School Education. This research includes the type of research and development (Research & Development). Data collection techniques used are observation, interviews, documentation and questionnaires. Data were analyzed through stages adapted to the ADDIE model, namely, analysis (analysis), design (design), development (development), implementation (implementation), evaluation (evaluation). The results of the development of animated media in the form of video based on the validation results of media experts show a feasibility percentage of 90.38% with very decent qualifications. The results of the material expert validation show that the percentage of eligibility level is 90.90% with very decent qualifications. The results of small-scale trials obtained 98.39% with very good qualifications. The results of large-scale trials obtained a percentage of 98.07% with very good qualifications.